Comparison of improved prognosis between hepatitis B‐ and hepatitis C‐related hepatocellular carcinoma. Issue 10 (3rd March 2015) - Minami, Tatsuya; Tateishi, Ryosuke; Shiina, Shuichiro; Nakagomi, Ryo; Kondo, Mayuko; Fujiwara, Naoto; Mikami, Shintaro; Sato, Masaya; Uchino, Koji; Enooku, Kenichiro; Nakagawa, Hayato; Asaoka, Yoshinari; et al.
Abstract : Aim: Treatment strategies for hepatocellular carcinoma (HCC) have been advanced. The aim of this study was to compare the change of the prognosis between hepatitis B‐related HCC (B‐HCC) and hepatitis C‐related HCC (C‐HCC) in the last two decades. Methods: We enrolled 166 B‐HCC patients who underwent percutaneous ablation between 1990 and 2009. Patients were divided into three groups according to the treatment time period: 1990–1995 (cohort 1, n  = 19), 1996–2002 (cohort 2, n  = 49) and 2003–2009 (cohort 3, n  = 98). We enrolled 1219 C‐HCC patients who underwent percutaneous ablation during the same period ( n  = 190, 413 and 616, respectively.). Interferon and nucleoside/nucleotide analog use was investigated. Prognosis was evaluated for each cohort using the Kaplan–Meier method and a multivariate Cox proportional hazard regression model. Results: Two (11%), 24 (49%) and 80 (82%) B‐HCC patients received nucleoside/nucleotide analogs during the follow‐up period in cohorts 1–3, respectively. Among them 1, 18 and 62 patients achieved viral remission, respectively. Thirty‐four (18%), 35 (8%) and 84 (14%) C‐HCC patients received interferon therapy, respectively. The 5‐year B‐HCC ( P  < 0.001) survival rates were 52.6%, 61.1% and 81.6% for cohorts 1–3, respectively. However, the survival rates were 55.6%, 58.8% and 61.1% for C‐HCC ( P  = 0.12), respectively. The B‐HCC prognosis improved dramatically ( P  < 0.001) over time, whereas the prognosis of C‐HCC improved moderately ( P  = 0.01). Conclusion: The prognosis of B‐HCC has improved dramatically over time, whereas that of C‐HCC has improved moderately.